Principle of Balance of Relationship Between Banks and Customers in Mudharabah Agreements - Nugroho, Ani (International Journal of Educational Research & Social Sciences, 2022)
Banks carry out their business activities in the form of accepting deposits in the form of savings and time deposits as well as conducting business activities by channeling funds in the form of financing and providing services in the form of remittances, save deposits and other banking services. Islamic banks in carrying out their business activities and functions, namely channeling funds in the form of providing financing to their customers, are carried out in the form of musharaka and mudharabah. The use of the mudharabah and musharaka principles is the main principle for Islamic banks. The research method used in this research is the normative legal method which is carried out by examining library materials, emphasizing on primary legal materials, namely legal materials consisting of basic regulations and legislation with an approach to legislation relating to with the principle of the balance of the relationship between the bank and the customer in the mudharabah financing contract, which is the implementation of the principle of good faith and the principle of freedom of contract which places the parties in a balanced manner (at-tawazun) with respect to their rights and obligations in determining the clauses of the contract contents.